Peningkatan Kualitas Layanan Staff Commercial Melalui Evaluasi Kerja - Sari, Desak Made Febri Purnama; Mananga, Christoper Hadi Aba (Jurnal Pengabdian kepada Masyarakat UBJ, 2024)
PT Angkasa Pura manages all airport services and airport related services. One division that has an important role is Airport Commercial. Airport commercial is part of a division of PT. Angkasa Pura I which has the responsibility to provide services and facilities that enhance customer experience and create additional revenue for the airport. To improve the quality of these services, PT Angkasa Pura I needs to evaluate the work of staff, especially in this airport commercial division. PT Angkasa Pura I conducts routine work evaluations to maintain and improve the quality of services provided to consumers. Suggestions that can be given to PT Angkasa Pura I are to continue to carry out routine work evaluations, carry out training and development programs, pay attention to and appreciate the positive attitudes and behavior of staff through programs, and pay attention to infrastructure and facilities to support optimal service.